Legal Review of Sharia Economics on the Practice of Rounding Weights in Palm Oil Trading in Mamuju Tengah Regency - Agussalim; Fadlan; Nuringsih; Abdul Rahman Aras (IECON: International Economics and Business Conference, 2025)
This study discusses the practice of rounding scales in palm oil sales transactions in Tasokko Village, Karossa District, Central Mamuju Regency, from the perspective of Sharia Economic Law. The main issue raised is how the practice of rounding scales is carried out by the weighing party, and how this practice affects the rights of farmers as sellers. This study uses a qualitative method with a descriptive approach. Data was collected through field observations and in-depth interviews with farmers and the weighing scale operators of UD. Pandang Raya. The research findings indicate that the practice of rounding weights is carried out by rounding the weighing results to the nearest ten, which often disadvantages farmers because the actual weight produced does not match the payment received. This contradicts the principles of justice (‘adl), honesty (sidq), and mutual consent (ridha) in Islamic Economic Law, which require that every transaction be conducted voluntarily, fairly, and without harming either party. This study recommends the need for supervision and improvement of the weighing system in the field, as well as education for farmers and collectors so that transactions are conducted in accordance with Sharia provisions. These findings are expected to serve as input for relevant parties to create transparent, fair, and blessed buying and selling practices in accordance with the principles of Islamic economics.